(untitled) - Redish, Edward F. (Hoboken, NJ, 2003)
A companion guide to using the Physics Suite, Teaching Physics is a book about learning to be a more effective physics teacher. It is meant for anyone who is interested in learning about recent developments in physics education. It is not a review of specific topics in physics with hints for how to teach them and lists of common student difficulties. Rather, it is a handbook with a variety of tools for improving both teaching and learning of physics from new kinds of homework and exam problems, to surveys for figuring out what has happened in your class, to tools for taking and analyzing data using computers and video.
Keywords: Physics,Physics; Physics,Study and teaching (higher),Study and teaching (secondary)